“Sichuanvirus”, a novel bacteriophage viral genus, able to lyse carbapenem-resistant Klebsiella pneumoniae - Juan Li; Qingqing Fang; Huan Luo; Yan Feng; Yu Feng; Zhiyong Zong (BMC Microbiology)
Abstract Background Carbapenem-resistant Klebsiella pneumoniae (CRKP) is a severe threat for human health and urgently needs new therapeutic approaches. Lytic bacteriophages (phages) are promising clinically viable therapeutic options against CRKP. We attempted to isolate lytic phages against CRKP of sequence type 11 and capsular type 64 (ST11-KL64), the predominant type in China. Results We recovered a lytic phage from sewage collected at a wastewater treatment station in Sichuan province, China. We obtained the genome of this phage and found that it is distinct from all known phages with the highest overall DNA similarity (12.5%, 16% coverage and 78.4% identity) with phage vB_EcoM_PHB05 (accession no. NC_052652) in ICTV. This phage represents a novel viral genus of the subfamily Stephanstirmvirinae, for which we proposed “Sichuanvirus” as the genus name. This phage has a narrow host range lyse specific for KL64 Klebsiella. This phage has no genes referring to antimicrobial resistance, virulence, and lysogen and is stable to a wide range of pH and temperatures. We also obtained three bacterial mutants resistant to the phage and performed genome sequencing for them. We therefore discovered that the interruption of a capsular polysaccharide biosynthesis-related gene wcaJ by insertion sequences mediated the resistance to this phage. Conclusion We recovered and characterized a phage of “Sichuanvirus”, a novel viral genus of subfamily Stephanstirmvirinae, which is suitable for phage therapy. The discovery of this phage expands the arsenal against CRKP.